2023
DOI: 10.1002/cjce.24795
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of inhomogeneous agglomerates for a fractal dimension of 2.5 at intermediate Reynolds numbers: Effect of agglomerate sizes and Reynolds numbers

Abstract: In this study, the effect of agglomerate sizes for a fractal dimension (D f ) of 2.5 on the hydrodynamics at intermediate Reynolds numbers (Re) of 1-120 was assessed. The results show that a core behaves like a solid sphere that exists in the central region inside the agglomerate. In addition, increasing the agglomerate diameter represents adding an extra permeable layer outside the agglomerate. For a larger Re or a smaller agglomerate diameter, the fluid can enter and penetrate through the agglomerate more ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This demonstrates that there is a solid-like central core inside FNPAs when considering RVPM. Previous studies ,, have reported that agglomerates that follow the particle-cluster regime have a relatively dense core structure. This solid-like central core results in a greater velocity attenuation as the fluid passes through.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This demonstrates that there is a solid-like central core inside FNPAs when considering RVPM. Previous studies ,, have reported that agglomerates that follow the particle-cluster regime have a relatively dense core structure. This solid-like central core results in a greater velocity attenuation as the fluid passes through.…”
Section: Resultsmentioning
confidence: 96%
“…The complex structure inside nanoparticle agglomerates is difficult to describe by standard (Euclidean) geometry . However, it has been reported in recent years that some nanoparticle agglomerates formed by the particle-cluster regime have fractal characteristics, ,,,,, and the structure within nanoparticle agglomerates is typically described in terms of fractal geometry. As shown in Figure , based on the fractal theory, nanoparticle agglomerates in this regime are claimed to be formed by smaller particles adding to the exterior of a “seed” agglomerate and its local porosity averaged over the length scale will vary with the radial distance .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation